2009
DOI: 10.1021/bm801240r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Bioengineered α-d-Glucans Produced by Mutant Glucansucrase GTF180 Enzymes of Lactobacillus reuteri Strain 180

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 28 publications
(136 reference statements)
3
64
0
Order By: Relevance
“…In GtfC homologs, the conserved residue W1065 (Gtf180 L. reuteri 180 numbering) is replaced by a Tyr, as is the case in GtfB-like 4,6-␣-glucanotransferases. Moreover, the amino acid residues at positions 1137, 1140, and 1141, known to be important for glucosidic linkage specificity in glucansucrases (28)(29)(30), are Gln, Lys, and Asn, respectively, in GtfC homologs, similar to GtfB-like 4,6-␣-glucanotransferases. Apart from the well-recognized I-to-IV homology regions, the three additional conserved regions (VI, V, and VII) proposed to be related to the maintenance of the structure and to a given enzyme specificity in GH13 family proteins (6,31,32) were identified in the GH70 and GH13 sequences.…”
Section: Resultsmentioning
confidence: 99%
“…In GtfC homologs, the conserved residue W1065 (Gtf180 L. reuteri 180 numbering) is replaced by a Tyr, as is the case in GtfB-like 4,6-␣-glucanotransferases. Moreover, the amino acid residues at positions 1137, 1140, and 1141, known to be important for glucosidic linkage specificity in glucansucrases (28)(29)(30), are Gln, Lys, and Asn, respectively, in GtfC homologs, similar to GtfB-like 4,6-␣-glucanotransferases. Apart from the well-recognized I-to-IV homology regions, the three additional conserved regions (VI, V, and VII) proposed to be related to the maintenance of the structure and to a given enzyme specificity in GH13 family proteins (6,31,32) were identified in the GH70 and GH13 sequences.…”
Section: Resultsmentioning
confidence: 99%
“…LB agar plates were made by adding 1.5% agar to the LB medium. The plasmid p15GTF180-⌬N-SX, containing N-terminally truncated GTF180 (residue 742-1772), was used for mutagenesis and protein production (27).…”
Section: Methodsmentioning
confidence: 99%
“…The relative intensity of the H-4 signal (t4, between ϳ␦ 3.40 and 3.45) stemming from terminal residues of ␣-glucan polysaccharides is an indicator for the amount of branching (Fig. 3b) (27,29,39). Examination of NMR spectra of polysaccharides produced by Ala-978 mutants with a larger side chain (A978L, A978P, A978F, and A978Y) revealed that the intensity of the t4 signal was reduced, indicating a decreased amount of branched linkages; those of Ala-978 mutations with a small amino acid resi-due (A978G and A978S) did not show such a change (Fig.…”
Section: Ala-978 Has An Important Role In Branched Linkage Formation-mentioning
confidence: 99%
See 1 more Smart Citation
“…Glc(a1 / 6) Glc(a1 / 3)Glc(a1 / 6)Glc [28]. Taking into account composite models of a-D-glucans generated from sucrose using wild-type and mutant Gtf180-DN glucansucrases as biocatalyst [28,30,31], the structure of one of the expected minor products is hypothesized to be an elongation of RebA-G2a with a Glc(a1 / 6) residue [Glc7(a1 / 6)Glc6(a1 / 6)Glc5(a1 / 6)Glc1(b1 / ].…”
Section: Structural Analysis Of Hplc Fraction F4mentioning
confidence: 99%